(untitled) (Eurasian Journal of Research, Development and Innovation, 2024)
Magnetic resonance (MR) imaging allows freedom in choosing oblique planes of section and rotation of image plane with respect to frequency encoded (F) and phase-encoded (P) dimensions. A general method is described for understanding geometric relationships between the fixed magnetic coordinate system, patient position and the flexible observers coordinate system. Oblique planes of section are clinically useful in studying organs with an axis symmetry that is oblique to magnet coordinate system, such as the heart. Rotation of image plane can be used to move motion artifacts away from anatomic regions of interest, such as the liver and spine. Appropriate use of oblique section and image rotation can improve MR image quality and diagnostic value of the patient study.